Crimes and Punishments, in Compiled and Revised Laws of the Territory of Idaho 354 (1875) - (:unkn) unknown (My University, 1875)
§ 133: Prohibited the carrying of "any pistol, gun, knife, dirk, bludgeon, or other offensive weapon, with intent to assault any person." Punishable by imprisonment for up to 3 months or a fine up to $100.
Keywords: CARRY - INTENT TO COMMIT CRIME